Establishment of expanded and streamlined pipeline of PITCh knock-in – a web-based design tool for MMEJ-mediated gene knock-in, PITCh designer, and the variations of PITCh, PITCh-TG and PITCh-KIKO. Issue 3 (4th May 2017) - Nakamae, Kazuki; Nishimura, Yuki; Takenaga, Mitsumasa; Nakade, Shota; Sakamoto, Naoaki; Ide, Hiroshi; Sakuma, Tetsushi; Yamamoto, Takashi
ABSTRACT: The emerging genome editing technology has enabled the creation of gene knock-in cells easily, efficiently, and rapidly, which has dramatically accelerated research in the field of mammalian functional genomics, including in humans. We recently developed a microhomology-mediated end-joining-based gene knock-in method, termed the PITCh system, and presented various examples of its application. Since the PITCh system only requires very short microhomologies (up to 40 bp) and single-guide RNA target sites on the donor vector, the targeting construct can be rapidly prepared compared with the conventional targeting vector for homologous recombination-based knock-in. Here, we established a streamlined pipeline to design and perform PITCh knock-in to further expand the availability of this method by creating web-based design software, PITCh designer (http://www.mls.sci.hiroshima-u.ac.jp/smg/PITChdesigner/index.html ), as well as presenting an experimental example of versatile gene cassette knock-in. PITCh designer can automatically design not only the appropriate microhomologies but also the primers to construct locus-specific donor vectors for PITCh knock-in. By using our newly established pipeline, a reporter cell line for monitoring endogenous gene expression, and transgenesis (TG) or knock-in/knockout (KIKO) cell line can be produced systematically. Using these new variations of PITCh, an exogenous promoter-driven gene cassette expressing fluorescent protein gene and drug resistance gene can be integrated into a safe harbor or a specific gene locus to create transgenic reporter cells (PITCh-TG) or knockout cells with reporter knock-in (PITCh-KIKO), respectively.